UNLOCKING UNDERSTANDING: EFFECTIVE STRATEGIES FOR ENHANCING LISTENING SKILLS IN EFL LEARNERS - Ibrokhimova Mokhinur Mukhammadkurbanovna (TADQIQOTLAR.UZ, 2024)
Abstract: Effective communication requires the ability to listen, especially when speaking English as a foreign language (EFL). In order to help EFL learners better grasp spoken English, this paper examines practical methods for improving listening comprehension. We start by recognizing typical difficulties that students encounter, like a little vocabulary, strange accents, and a lack of exposure to real listening resources. A variety of instructional strategies are then presented in the paper, such as the utilization of real audio resources, pre-listening exercises that draw on past knowledge, and post-listening assignments that encourage introspection and critical thinking.